Religious Responses to Covid-19 in England: An Analysis of the Key Socio-Legal Themes - Amin Al-Astewani (Millah: Journal of Religious Studies, 2023)
Religious responses to Covid-19 raised several far-reaching questions with a number of socio-legal implications. How does the historical tension between science, politics and religion manifest itself in global pandemics? What ethical and human rights issues are at play as a health crisis unfolds, and what is the role of the media in mitigating such issues? Finally, how significant is the pastoral role which is thrust upon religious leaders in times of crisis, and how should this role be understood in the materialistic and secular modern era? This article addresses such questions within the specific context of England. It builds upon previous research by the author on the responses of the British Muslim community to the Covid-19 pandemic, by expanding the analysis to explore the broader socio-legal themes that emerged within religious responses to Covid-19 in England.